Se(XY) matters: the importance of incorporating sex in microphysiological models. Issue 11 (November 2022) - Kouthouridis, Sonya; Robson, Eleanor; Hartung, Alicia; Raha, Sandeep; Zhang, Boyang
Abstract : The development of microphysiological models is currently at the forefront of preclinical research. Although these 3D tissue models are being developed to mimic physiological organ function and diseases, which are often sexually dimorphic, sex is usually neglected as a biological variable. For decades, national research agencies have required government-funded clinical trials to include both male and female participants as a means of eliminating male bias. However, this is not the case in preclinical trials, which have been shown to favor male rodents in animal studies and male cell types in in vitro studies. In this Opinion, we highlight the importance of considering sex as a biological variable and outline five approaches for incorporating sex-specific features into current microphysiological models. Highlights: There is a bias towards male cells and animal models in preclinical research which can lead to increased risk to female participants in clinical trials. Incorporating sex-specific functions into microphysiological models will allow the assessment of sexually dimorphic cell and organ function, disease, and drug response at the preclinical stage. Techniques for incorporating sex in microphysiological models include the selection of cell sex, the modeling of sexually dimorphic organ structures, the addition of hormones in culture, the modeling of reproductive organs and their inclusion in body-on-a-chip systems. Advances in cell culture, microfluidics, and biofabrication are required to incorporate sex-specific features to organoid, organ-on-a-chip, and body-on-a-chip systems..